Culturally responsive education under ESSA: A state-by-state snapshot. (October 2019) - Schettino, Isabela; Radvany, Katie; Wells, Amy Stuart
A map created from data compiled by Isabela Schettino and Katie Radvany at the Reimagining Education: Teaching and Learning in Racially Diverse Schools Summer Institute (held at Teachers College, Columbia University, and directed by Amy Stuart Wells) shows which states have included references to culturally responsive teaching practices in the ESSA plans submitted to the Department of Education .